Pengembangan Sistem Informasi di Sektor Konstruksi Menggunakan Pendekatan Rapid Application Development (RAD) - Nur Wahida Putri, Ahda; Mohamad Nur Yorisyah; Ihsan Sabila Khan M, Fathi; Harits, Dimaz (SURYA TEKNIKA, 2025)
PT XYZ is a construction company specializing in planning and executing residential and commercial projects. To support project management, administration, and customer services, this study developed an information system using the Rapid Application Development (RAD) approach. RAD was selected for its advantage in accelerating system development through an iterative, user-focused process. The resulting system features online booking, project status tracking, and digital payment, designed to improve operational efficiency and service transparency. Evaluation results indicate that the system successfully integrates various functions, minimizes administrative errors, and expedites business processes. This implementation provides significant benefits for PT XYZ by enhancing service quality and competitiveness in the digital era.